New Approach to Calibration of Vertical Fuel Tanks - Knyva, V.; Knyva, M.; Rainys, J. (Elektronika ir Elektrotechnika, 2013)
Recalibration of the vertical fuel tanks must be done once in 5 years. Fuel tank during its usage can be affected by geological or other reasons (for example it may be damaged during installation or repair). So Volume chart of the tank can be corrupted. For calibration of vertical fuel tanks in Lithuania and in all EU, mix of geometrical and liquid filled methods is used. In this article a new approach to calibration of vertical fuel tanks, based on 3D laser scanning and data processing, will be presented. DOI: http://dx.doi.org/10.5755/j01.eee.19.8.5391